Frasa Bahasa Mairasi: Phrases in Mairasi Language - Antonius Maturbongs (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
Phrase only filling one function in clause. To strengthen clarification above cited one congeniality [of] phrase supporting [it] made by Elson Pickket and (1976: 73), namely " Phrase composed unit a in A, potentially, words more or two or, typically which but, always note but, level clouse a of slot fills." Implicit here congeniality that frase only have potency [to] consist of two word or more and clearly [do] not exceed clause characteristic namely only one function except predikat [relation/link] and object in consequence phrase to represent gatra filler in clause. This congeniality [is] weared as basis for identify phrase in this research analyze.  Starting from theory weared in this research namely analyse tagmemik, hence discussion hereinafter will be divided into function analysis, category, and role of [is] each phrase interior.